Wolf - Hayder, Mo (Atlantic Monthly Press, 2014)
"When a vagrant--the Walking Man--finds a dog wandering alone with a scrap of paper with the words "HELP US" attached to its collar, he's sure it's a desperate plea from someone in trouble and calls on Detective Inspector Jack Caffery to investigate. Caffery is reluctant to get involved--until the Walking Man promises new information regarding the childhood abduction of Caffery's brother in exchange for the detective's help tracking down the dog's owners. Caffery has no idea who or what he is searching for, but one thing he is sure of: it's a race against time. Meanwhile a wealthy local family is fighting for their lives, held hostage in their remote home. As their ordeal becomes increasingly bizarre and humiliating, the family begins to wonder: Is this really a random crime?" -- from publisher's web site.